(untitled) (CAHIERS MAGELLANES-NS, 2024)
Cyberbullying and Cyberstalking have emerged as significant threats in the digital age, necessitating comprehensive legal measures to safeguard individuals from online harassment and abuse. This article explores the definitions, features, objectives, and prevention strategies related to Cyberbullying and Cyberstalking. It also delves into the importance of addressing these Cybercrimes and the existing legal framework in India. Cyberbullying and Cyberstalking have become increasingly prevalent in India due to the widespread use of the internet and social media platforms. The use of digital technology to harass, intimidate, or threaten individuals has become a serious problem, particularly among young people. The consequences of Cyberbullying and Cyberstalking can be devastating, leading to depression, anxiety, and even suicide in some cases. The legal framework in India to address Cyberbullying and Cyberstalking is still evolving. The Information Technology Act, 2000 (IT Act) and the Indian Penal Code, 1860 (IPC) provide some provisions to address these issues, but they are not comprehensive enough to deal with the complex and varied forms of Cyberbullying and Cyberstalking. There is a need for greater awareness and education about these issues among young people, parents, and educators. Additionally, the police and the judiciary need to be trained to deal with these cases effectively. There is also a need for stronger laws and regulations to address Cyberbullying and Cyberstalking, as well as greater cooperation between the government, social media companies, and other stakeholders to tackle this problem. In conclusion, Cyberbullying and Cyberstalking are serious issues in India that require urgent attention. Legal conferences can play a vital role in raising awareness, identifying gaps in the legal framework, and proposing solutions to address these issues effectively.